Integrated Monitoring Framework for Climate-Smart Agriculture: Hoima Climate Smart Villages, Uganda - Ambaw, Gebermedihin; Recha, John W.M.; Radeny, Maren A.O.; Kakeeto, Ronald; Baguma, Sylvester Dickson; Bonilla Findji, Osana; Eitzinger, Anton; Andrieu Charron, Nadine Veronique; Solomon, Dawit (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
To help agricultural communities in Uganda deal with climate related challenges, the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) developed the Climate-Smart Villages (CSVs) Research for Development (R4D) approach in western Uganda’s Hoima district in 2012. Using participatory methods, testing of technological and institutional options for dealing with climate change in agriculture was undertaken in Hoima, with the aim of scaling the appropriate options and drawing out lessons for policymakers from local to national levels.